Gloss to the resolution of the Supreme Court of 13 April 2023, III CZP 125/22 - Jasiakiewicz, Tomasz (Studia Iuridica Toruniensia, 2026)
In the thesis to the resolution under comment, the Supreme Court accepted that a claim resulting from a legitim shall devolve upon an heir of the person entitled to that legitim only if that heir is one of the persons entitled to a legitim from the first deceased (Article 1002 of the Civil Code). The resolution is another decision in which the Supreme Court did not allow the catalogue of persons entitled to inherit a claim resulting from a legitim (indicated in the provision of Article 1002 of the Civil Code) to be expanded. The position of the Supreme Court formulated in this way deserves approval. On the other hand, doubts are raised by the justification of the resolution, in which the claim resulting from the legitim was not recognised by the Court as a right of a personal nature. Indeed, with such an interpretation, Article 1002 of the Civil Code would have to be regarded as an unconstitutional, inconsistent and illogical provision. Contrary to the position of the Supreme Court, only an interpretation taking into account the close connection of the claim resulting from the legitim with the person of the testator allows reconciling the content of Article 1002 of the Civil Code with the constitutional principles of protection of the right of inheritance, freedom of testation and the principle of equality.